The Scottish National Party and the Economics of Nationalism: from Oil to Renewables? - Edwige Camp-Pietrain (Revue LISA)
The SNP’s nationalism is based on Scotland’s economic resources, especially oil. Such a strategy helped the party gain representation in the House of Commons from the 1970s and was still regarded as an asset in the run-up to the 2014 referendum on independence. However, in the following months, the SNP had to admit that an independent Scotland could no longer rely on declining oil and gas revenues to balance its books and would have to turn to renewables. This U-turn has reinforced the international outlook of the party’s nationalism—both for resource management and for cooperation with other countries.